From vogue words to lexicalized intensifying words: the renewal and recycling of intensifiers in English. A case-study of very, really, so and totally - Lucile Bordet (Lexis: Journal in English Lexicology)
This paper investigates the renewal of intensifiers in English. Intensifiers are popularized because of their intensifying potential but through frequency of use they lose their force. That is when the renewal process occurs and promotes new adverbs to the rank of intensifiers. This has consequences on language register. “Older” intensifiers are not entirely replaced by fresher intensifiers. They remain in use, but are assigned new functions in different contexts. My assumption is that intensifiers that have recently emerged tend to bear on parts of speech belonging to colloquial language, while older intensifiers modify parts of speech belonging mostly to the standard or formal registers. There seems to be a correlation between the intensifying force of an adverb and language register.